1992
DOI: 10.1093/bja/69.5.444
|View full text |Cite
|
Sign up to set email alerts
|

Etomidate Shortens the Onset Time of Neuromuscular Block

Abstract: We have studied 30 healthy patients allocated randomly to receive thiopentone, propofol or etomidate in equipotent doses followed by vecuronium 0.1 mg kg-1. Haemodynamic variables and time to 100% neuromuscular block were measured. The patients receiving etomidate had a significantly shorter onset time of neuromuscular block compared with those receiving the two other i.v. induction agents. There was a significant negative correlation between onset time of neuromuscular block and the maximum percent change in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 8 publications
0
22
0
3
Order By: Relevance
“…3 Also, the onset time of neuromuscular blockade can be modified by the sedative. 4 This is particularly important in the context of our study because ketamine has a longer onset of effect compared to etomidate. Therefore, if intubation is attempted prior to maximal neuromuscular blockade, intubation success could be affected.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…3 Also, the onset time of neuromuscular blockade can be modified by the sedative. 4 This is particularly important in the context of our study because ketamine has a longer onset of effect compared to etomidate. Therefore, if intubation is attempted prior to maximal neuromuscular blockade, intubation success could be affected.…”
Section: Discussionmentioning
confidence: 93%
“…[3][4][5] In previous systematic reviews and registry studies, the effect of the paralytic on intubation conditions was modified based on the sedative used. 2,5 This suggests that sedative selection could also influence intubation success, which is a more clinically relevant outcome compared to intubation conditions.…”
mentioning
confidence: 99%
“…They have suggested that ephedrine might have increased cardiac output and muscle blood flow [14]. Gill and Scott [15] have also reported that the onset time of vecuronium is shorter when etomidate is used for induction compared to thiopental sodium because of the lesser hemodynamic depression of etomidate than thiopental sodium. Thus, we compared the onset time of rocuronium in this study according to the induction drug used.…”
Section: Discussionmentioning
confidence: 99%
“…As condições de intubação traqueal dependem de vários fatores, dentre eles o agente de indução, o uso de opióides e a dose de bloqueador neuromuscular [13][14][15] . Em animais de experimentação, os agentes de indução não mostram interferência na potência do rocurônio 16 .…”
Section: Discussionunclassified
“…Clinical criteria, and not neuromuscular transmission monitors, have been indicated to evaluate tracheal intubation since masseter and diaphragm relaxation and anesthetic depth are better determinants of tracheal intubation conditions than adductor policis muscle relaxation 11,12 . Tracheal intubation conditions depend on several factors, among them the induction agent, the use of opioids and neuromuscular blocker dose [13][14][15] . In experimental animals, induction agents do not interfere with rocuronium potency 16 .…”
Section: Discussionmentioning
confidence: 99%